TRADITIONS OF THE SAK-MASSAGET TRIBES (American Journal of Interdisciplinary Research and Development, 2024)
The article consists of a scientific analysis of the special traditions of the Sak-Massaget tribes who lived in the ancient Central Asian region in the VIII-IV centuries BC based on the works of historians of ancient times and modern historians.